In-service Professional Development and Constructivist Curriculum: Effects on Quality of Child Care, Teacher Beliefs, and Interactions - Howe, Nina; Jacobs, Ellen; Vukelich, Goranka; Recchia, Holly (Alberta Journal of Educational Research, 2012)
The purpose of this study was to assess three methods of delivering in-service professional development regarding constructivist curriculum for early childhood educators. Educators in 44 not-for-profit child care centres in three Canadian cities were studied; 94 educators with formal preservice training participated. The three methods were (a) a consultant model, (b) workshops, and (c) a readings group. Global classroom quality was assessed with the Early Childhood Environment Rating Scale-Revised ([ECERS-R], Harms, Clifford, & Cryer, 2005), educators were interviewed about their beliefs regarding curriculum, and modified running record observations of educator-child interactions (i.e., guidance, directives) were assessed before and after the 15-week intervention. Over time the consultant model was associated with an increase in guidance interaction (i.e., promoting children’s learning and development). A number of findings related to site were evident for quality of child care and educator beliefs, and highlight the challenges associated with conducting multi-site research studies. Implications for providing in-service professional development regarding curriculum are discussed. L’objectif de cette étude était d’évaluer trois méthodes de prestation de développement professionnel offert sur place et portant sur un programme d’études constructiviste pour éducateurs de la petite enfance. Quatre-vingt-quatorze éducateurs avec une formation d’orientation formelle et provenant de 44 garderies sans but lucratif dans trois villes canadiennes ont participé à l’étude. Les trois méthodes employées étaient les suivantes : (a) un modèle de consultation, (b) des ateliers et (c) un groupe de lectures. Nous avons évalué la qualité globale de la classe d’après l’échelle d’évaluation révisée du milieu d’apprentissage de la petite enfance (Early Childhood Environment Rating Scale-Revised, Harms, Clifford, & Cryer, 2005), passé en entrevue les éducateurs pour connaitre leurs croyances par rapport au programme d’études et évalué, avant et après les 15 semaines d’intervention, des fiches d’observation individualisée modifiées portant sur les interactions entre l’éducateur et les enfants (conseils, directives). À la longue, un lien s’est établi entre le modèle de consultation et une augmentation de l’interaction impliquant des conseils (stimulation du développement et de l’apprentissage des enfants). Plusieurs des conclusions liées au site étaient évidentes en ce qui concerne la qualité de la garde des enfants et les croyances des éducateurs, et elles font ressortir les défis découlant des projets de recherche impliquant plusieurs sites. Nous évoquons les implications de fournir du développement professionnel portant sur les programmes d’études.